AAGBI core topics in anaesthesia 2015 - Harrop-Griffiths, William; Griffiths, Richard, 1960-; Plaat, Felicity; Association of Anaesthetists of Great Britain and Ireland (Chichester, West Sussex, UK ; Hoboken, NJ, USA : John Wiley & Sons Inc., 2015)
Based on the Association of Anaesthetists of Great Britain & Ireland's (AAGBI) continuing education lecture series, this clinically-oriented book covers the latest developments in research and the clinical application of anesthesia and pain control. Reviews latest developments in research and practice Clinically-oriented but rooted in basic science Concise and informative articles on key topics Road-tested through CPD roadshows Designed specifically for continuing medical education
Abnormalities of coagulation and obstetric anaesthesia / Hilary Swales -- Acute coronary syndromes and anaesthesia / Yasir Parviz, Rachel Orme, Oliver Watson, and Tim Chico -- Acute pain management of opioid tolerant patients / Mark Jackson -- Echocardiography and anaesthesia / Jonathan H. Rosser and Nicholas J. Morgan-Hughes -- Medico-legal aspects of regional anaesthesia / William T. Frame -- Peri-operative use of beta-blockers : yes or no? / Nanda Gopal Mandal -- Transfusion requirements and the older person / Alexa Mannings and Iain Moppett -- Organ donation and the anaesthetist / Dale Gardiner, Neal Beckett, Paul Townsley, and Helen Fenner -- Postoperative cognitive dysfunction : fact or fiction? / Irwin Foo -- Pre-operative anaemia : should we worry? / Robert Kong.
Continuation of: AAGBI core topics in anaesthesia / edited by Ian Johnston, William Harrop-Griffiths, Leslie Gemmell. 2012.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Anesthesia; Anesthesia -- Methods; Anesthesia -- contraindications; Surgical Procedures, Operative; Electronic books; Electronic books